The Differences Fracture Resistance between Smooth and Serrated Type of Fiber Reinforced Composite Post - Widyastuti, Noor Hafida; Isabella, Dara (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2020)
Purpose: to determine fracture resistance differences between smooth type fiber reinforced composite post and serrated types.Methodology: the design of research is post test only control group design. The sample were 32 extracted mandibullary premolars treated endodontically crown down method with gutta percha and resin sealer. The tooth after root canal treatment is continued with the preparation of the post using precission drill. The samples divided into two group based: A. smooth type FRC post, B. serrated type FRC post. FracturSamples were loaded to failure with a Universal Testing Machine. Results: there was a fracture resistance difference between smooth type of FRC post and serrated. Fiber reinforced composite type serrated is more resistance to fracture than FRC type smooth.